Pengaruh Metode Pembelajaran Scramble terhadap Kemampuan Mengenal Huruf di Taman Kanak-kanak - Andana, Nora Rizki; Pransiska, Rismareni; Yetti, Rivda (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
This study aims to determine the influence of the Scramble learning methods on introducing letters of child. The research method used is quantitative in the form of experiment quasy. The results showed that the children’s in the experiment class used Scramble learning methods had a higher average compared to the control class that used Flashcard methods. The average number of the experimental class is 92,5 and the average number of the control class is 82.5. Based on the data analysis that has been done that thitung>ttabel, is 2.469> 2, 10092. There for can be concluded that scramble learning methods on introducing letters of child.